Virtual Laboratory Based Guided Inquiry: Viscosity Exsperiments - Wawan Kurniawan; Jufrida Jufrida; Fibrika Rahmat Basuki; Rima Ariani; Olva Fitaloka (STKIP Singkawang, 2019)
This study aims to develop a virtual laboratory (Vir-lab) based guided inquiry on viscosity experiments and know the students' perceptions of the products developed. This study was a research and development using 4D model that consists of four stage: define, design, develop, disseminate. The participants were two material experts, two media experts, and 43 students. Data collection used expert assessment sheet and student response questionnaire. The data were analyzed descriptively. The result of this study was a Vir-lab which was packaged in e-book form with 3D effects. The activities in the Vir-lab are designed based on the syntax of guided inquiry. The Vir-lab contains goals, problem formulations, theories, hypotheses, tutorial videos, virtual experiments, experimental data, data analysis, results, and conclusions. The results of the material expert obtained a score of 45 with a very good category and media experts obtained a score of 66 with a very good category, and the results of the students' perception test obtained a score of 60.65 with a very good category. The conclusion of this study shows that the Vir-lab is valid and suitable for use as a medium for learning physics.